THE EFFECTIVENESS OF THE GUIDANCE PROCESS THESIS ONLINE UPI MECHANICAL ENGINEERING EDUCATION STUDENTS DURING THE COVID-19 - khair, ghalib abul; Darmawan, Bambang; Purnawan, Purnawan; Maharis, Ikhsan Juliansyah (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2021)
Indonesia is one of the countries that has been affected by the Covid-19 virus. The Covid-19 pandemic has disrupted the education sector in Indonesia, resulting in the government changing the learning system, which is usually face-to-face, now into long-distance through an online learning system. So seeing a situation like this requires information about the effectiveness of the online learning process during the Covid-19 pandemic. Not only is the learning process online, but the TA guidance process must also be online. This study aims to determine aspects of the online TA guidance process, namely the behavior of lecturers, media guidance, time utilization, and student behavior. The research method used is descriptive quantitative method and the data were obtained through a survey. The subjects of this study were students of 2016 and 2017 at PTM who experienced an online TA guidance process during the Covid-19 pandemic. The research sample was 117 students. The results of this study are, the online TA guidance process of PTM students is quite effective, including aspects of lecturer behavior and aspects of guidance media, while aspects of time utilization and aspects of student behavior are in the ineffective category.